The effect of oral motor activity on the athletic performance of professional golfers - Ringhof, Steffen; Hellmann, Daniel; Meier, Florian; Etz, Eike; Schindler, Hans J.; Stein, Thorsten (Frontiers in Psychology, 2015)
Human motor control is based on complex sensorimotor processes. Recent research has shown that neuromuscular activity of the craniomandibular system (CMS) might affect human motor control. In particular, improvements in postural stability and muscle strength have been observed as a result of voluntary jaw clenching. Potential benefits of jaw aligning appliances on muscle strength and golf performance have also been described. These reports are highly contradictory, however, and the oral motor task performed is often unclear. The purpose of our study was, therefore, to investigate the effect of submaximum biting on golf performance via shot precision and shot length over three different distances. Participants were 14 male professional golfers – seven with sleep bruxism and seven without – randomly performing golf shots over 60 m, 160 m, or driving distance while either biting on an oral splint or biting on their teeth; habitual jaw position served as the control condition. Statistical analysis revealed that oral motor activity did not systematically affect golf performance in respect of shot precision or shot length for 60 m, 160 m, or driving distance. These findings were reinforced by impact variables such as club head speed and ball speed, which were, also, not indicative of significant effects. The results thus showed that the strength improvements and stabilizing effects described previously are, apparently, not transferable to such coordination-demanding sports as golf. This could be due to the divergent motor demands associated with postural control and muscle strength on the one hand and the complex coordination of a golf swing on the other. Interestingly, subjects without sleep bruxism performed significantly better at the short distance (60 m) than those with bruxism. Because of the multifactorial etiology of parafunctional CMS activity, conclusions about the need for dental treatment to improve sports performance are, however, completely unwarranted.